Insomnia and microbiota: clinical and pathophysiological relationships - V. A. Akhmedov; T. N. Fedorova; A. S. Isaeva (Лечащий Врач)
Background. The gut microbiota plays an important role in maintaining human health. The brain-gut axis is currently being actively studied. During the research, it was noted that the intestinal microbiota demonstrates circadian rhythms that interact with the circadian rhythms of the host. Chronic insomnia, in turn, can disrupt microbial circadian rhythms, thereby affecting the composition and function of the intestinal microbiota. Jet lag syndrome causes a significant increase in body weight and blood glucose levels due to its effect on the composition of the human intestinal microbiome. With the change of day and night, the number of Paraprevotella, Fusobacteria and Fusobacteriales in the intestinal microflora increases. The vagus nerve, interacting with the intestinal nervous system, releases nicotinic cholinergic signals to activate intestinal glial cells, which can secrete S-nitrosoglutathione to increase the expression of tight junctional proteins. 5-hydroxytryptamine (5-HT) is an inhibitory neurotransmitter that is synthesized and distributed by about 90% in enterochromaffin cells. Sleep disorders occur when the level of 5-HT in the brain decreases. Currently, it has been proven that dysbiosis of the intestinal microbiota is associated with the development of neuropsychiatric diseases and has a significant impact on human metabolic health. The gut microbiota plays an important role in the bidirectional connection between the brain, the immune system, and the gut (the brain-gut-immunity axis). On the one hand, the microbiota stimulates innate immunity by activating lymphoid tissues located in the intestinal system; on the other hand, interactions between bacterial fragments and receptors (such as TLR9 and the inflammasome) on the surface of epithelial and immune cells activate specific systemic and local immune responses.Results. The review article presents current data on the mechanisms by which the intestinal microbiota can influence the mental state and quality of sleep and the circadian rhythm of the host, and the role of regular stress on the composition of the microbiota is noted. Strategies have been outlined to improve sleep quality based on lifestyle adjustments, individual nutrition, prebiotics and "psychobiotics" to counteract dysbiosis, potentially associated with sleep disorders.